2014
DOI: 10.2478/s13536-013-0193-6
|View full text |Cite
|
Sign up to set email alerts
|

CVD synthesis of graphene nanoplates on MgO support

Abstract: Synthesis of graphene directly on MgO has been carried out and the structural properties of the obtained material have been investigated. Few-layered graphene was produced by simple thermal decomposition of methane over MgO powder at 950°C in a CVD reactor. The samples were purified by 10 N HNO 3 treatment, and studied by TEM, Raman spectroscopy, EDAX and SEM. TEM clearly indicated the formation of graphene. EDAX showed that the purified sample contained only carbon and no traces of MgO. The characteristic Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…SGNs synthesis was carried out using CVD method with methane as the carbon precursor according to the reference reported [21,22]. The CVD setup (FURNACE 1,200°C, Tianjin Zhong Ring Experimental Electric Furnace Co., Ltd.) contains a horizontal tubular furnace and gas flow control unit.…”
Section: Synthesis Of Tio 2 /Sgns Compositesmentioning
confidence: 99%
“…SGNs synthesis was carried out using CVD method with methane as the carbon precursor according to the reference reported [21,22]. The CVD setup (FURNACE 1,200°C, Tianjin Zhong Ring Experimental Electric Furnace Co., Ltd.) contains a horizontal tubular furnace and gas flow control unit.…”
Section: Synthesis Of Tio 2 /Sgns Compositesmentioning
confidence: 99%
“…[15] Experimental studies have shown that single-and multilayer graphene films can be grown directly on MgO substrates. [16][17][18][19][20][21][22] Gaddam et al, [16] prepared a single-layer graphene film on MgO(111) surface by the CVD method, and they found that the strong interaction between graphene and MgO can open the bandgap of graphene. Jerng et al, [18] used molecular beam epitaxy to directly grow graphene films on MgO (100) surface, and they observed clear D, G, and 2D bands by Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%